2014
DOI: 10.9755/ejfa.v26i12.19118
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of NaCl and seawater on germination of quinoa seed (Chenopodium quinoa willd)

Abstract: In this study the effect of NaCl and seawater, compared to a control with distilled water, on the seed germination of Chenopodium quinoa were investigated. All seeds germinated in all treatments: control and both NaCl and seawater treatments. However saline treatments delayed germination compared to the control seawater causing more delay than NaCl. The hypocotyls and radicle lengths and dry weights were affected more by NaCl than by seawater. The radicles were the most affected by salt stress compared to hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…quinoa ; It was previously found that C . quinoa seeds could germinate and start growing under relatively high salinity in 200 mM NaCl and 40% seawater [ 48 ]. Salinity influences seed germination by imposing osmotic stress, which limits water uptake by seeds, resulting in insufficient moisture to start the internal biochemical processes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…quinoa ; It was previously found that C . quinoa seeds could germinate and start growing under relatively high salinity in 200 mM NaCl and 40% seawater [ 48 ]. Salinity influences seed germination by imposing osmotic stress, which limits water uptake by seeds, resulting in insufficient moisture to start the internal biochemical processes [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three cultivars of quinoa (Titicaca, Puno, Vikinga) originating from Denmark were chosen to be studied for their ability to germinate under the stress of two salts known for causing salinity in soils (NaCl and Na 2 SO 4 ) and one salt responsible for alkalinity-Na 2 CO 3 . Most of the studies are focusing on the tolerance of quinoa, especially of Titicaca cultivar, to NaCl [6,10,12,13,26], one of the main factors for soil salinity [27], but little is known about the ability of quinoa seeds to germinate under Na 2 SO 4 or Na 2 CO 3 stresses [28]. Knowing the differences in quinoa's tolerance to chloride and sulfate salinity can bring important information for a more precise use of this crop in lands affected by soil salinity.…”
Section: Salinity and Alkalinity Effect On The Germination Of The Seedsmentioning
confidence: 99%
“…No differences were observed between the proline content of the seeds regardless of the concentrations used and the cultivar (Table 1). Usually, the salt induced inhibition of seed germination can be attributed to osmotic stress as a result of the decreasing rate of water uptake, or to ion toxicity as a consequence of the excessive intake of ions such as Na + which may change certain enzymatic or hormonal activities inside the seed [12,26,40,41]. Instead, alkaline stress, even if it has the same ion (Na + ) as saline stress factor, the added influence of high pH stress enhance the osmotic and ionic toxicity on seeds, but also can destroy the embryo [9].…”
Section: Tolerance Of Quinoa Cultivars To the Salt And Alkali Stressmentioning
confidence: 99%
“…Most of the previously referred studies have been carried out in quinoa germination and seedling growth responses under the control growth chambers. It is important to understand that germination and early seedling establishment stage is critical in the life cycle of plants, and many colleagues have documented these phenomena [ 34 , 35 ]. However, yield response factors of different quinoa genotypes to saline and marginal soil environment and their salinity tolerance mechanisms that may regulate seedling growth, yield and grain quality attributes need to be evaluated under marginal and nutrient poor sandy soils.…”
Section: Introductionmentioning
confidence: 99%